Law of agency "agency of necessity". Its' scope in Malaysia / Megat Mohamad Anuar Megat Noh - Megat Noh, Megat Mohamad Anuar (Faculty of Law, 1987)
Agency is the relationship which exist between two parties, one of whom expressly or impliedly consented that the other should represent him or act on his behaIf, and the other party is whom similarly consented to represent the former to act on certain task. 1 The person whose behalf the act is to be done is called the principal 2, while the person who is to represent the principal is called the Agent. 3 There are certain circumstances that the use of agency is needed. Ball and Rose in principles of business law4 has stated certain circumstances on which the role of agency is needed, such as for: i. physical necessity, ii. specialist knowledge, iii. in matter of identity iv. problems in transportation, emergency However, not in all cases that an agency can be said to be as an agency within the meaning stated under the law. The term "agency" has a different meaning between the legal use and that from the commerc iaI ones. Markesinis and Munday5 has stated that: " ..... it should be clear that the law of agency does not come into play everytime one person represents another. For example, no rules of agency apply when a husband sends his wife to a wedding to congratulate the newly-weds . For the ru les of agency to come into play the representation of one person by another must be meant to affect the principal's legal position ..... "